Assessment of conversion methods to acquire 1-minute integration time rain intensity statistic - Khairolanuar, Muhamad Haziq; Ismail, Ahmad Fadzil; Jusoh, Ahmad Zamani; Mohd Sobli, Nuurul Hudaa; Badron, Khairayu (Springer, 2015)
This paper presents some preliminary findings of assessments carried out pertaining to the applicability of rain intensity conversion methods. Five conversion methods were identified in this study namely the ITU-R, Segal, Burgeuno, Chebil-Rahman and Khairolanuar et al. 1 year of rain intensity data were acquired from the Malaysian Meteorological Department (MMD) and utilized in the investigation. The research methodology involves productions of annual rain intensity cumulative distributions at 1-minute integration time using mentioned conversion methods. Predicted values established by ITU-R are used as benchmark. The values are then compared with values acquired using other conversion methods; in order to validate the applicability and effectiveness of each method. Based on the evaluation, it can be observed that the Khairolanuar et al. method seems to be a befitting conversion method and capable of generating values with smallest percentage difference.